Petrografia, química mineral, datação e caraterização tecnológica dos granulitos da região de Macaco — Itapipoca (CE) - Nascimento, Magnolia Barbosa do (2006)
The study area is constituted by an assembly formed by biotite gneiss with hornblende, granulites (enderbites and charnockites), granodiorites, monzogranites, granodiorites with garnet and dikes (sienogranites) and alluvium colluvial deposits. The mineral metamorphic association representative of the biotite gneiss with hornblende is formed by biotite + hornblende + plagioclase + potassic feldspar + quartz, establishing conditions of P and T compatible to the Anfibolite facies. The values of P for those litotipos are between 5,8 to 7,1 kbar and the temperatures around 707°C on average. The granodiorites showed values of pressure of 7,68Kbar on average. The temperatures calculated for those litotipos stayed around 764°C. In the granodiorites with garnet in pressure medium found was of 9,15Kbar and temperatures medium of 837°C. The isotopyc analyses did used method Sm/Nd (TpM) and U/Pb in zircon in charnockite resulted in the value of s (t) = —2,349, for an age Sm/Nd (TDM) de 2,56Ga and an age U/Pb de 2092 ± 11 Ma, that negative value of s (t) indicates that had a process of crustal reworking and probably this granulite does not represent the base of magmatic arc of Santa Quitéria. The technological characterization did in the enderbites of the area followed specific norms by ABNT and ASTM. For the physical-mechanical analysis results obtained are: physical indexes (specific gravity 2,844 and 2,849kg/m3; porosity 0,49°i ; water absorption 0,17%); simple uniaxial compression resistance 175,09 and 160,19MPa; flexural resistance, 15,06 and 13,71MPa and (Amsler) abrasive wear, 0,77 and 0,94mm. In the weathering test (chemical attack) the biggest loss of brilliance occurred in the attack by potassium hydroxide while the smallest loss was caused by the addition of the chloridric acid. The petrographics aspects and the results of physical and physical-mechanical tests suggest a potential use of this rocks as both dimension and covering stones in construction purposes.